The pottery vessel from site 5LA3189: A possible Navajo vessel from southeastern Colorado. (May 2014) - Krause, Richard A.
Abstract : In April 2005 a ceramic vessel from site 5LA3189 in southeastern Colorado's Piñon Canyon was analyzed at Fort Carson's Directorate of Environmental Compliance and Management laboratory. The analysis was the first step in classifying the specimen. When the existing classification system failed to provide adequate criteria to classify the vessel, a new Front Range Ware was defined in an attempt to do so. When Front Range Ware also failed to provide adequate criteria to classify the specimen, ethnographic information and manufacturing data were used to propose a Navajo identity. A Navajo origin was suggestive but not conclusive. Nevertheless, the analysis illustrates an approach to the study of ceramics that can, when combined with appropriate physical and chemical tests, provide the quantitative and qualitative data needed to assign an ethnic identity to archeological specimens.